Preliminary Study of Dominance and Ethnobotany of Medicinal Plants on the Mayung Polak Trail, Mount Rinjani National Park - Valentino, Niechi; Prasetyo, Andrie Ridzki; Firdaus, Rato Silamon; Araruna, Isroqul Ihsan (LITPAM, 2025)
This research examines the ecological dominance and ethnobotanical potential of medicinal plants found along the Mayung Polak Waterfall Trail, located in the Timbanuh Resort of Mount Rinjani National Park (MRNP). By combining vegetation analysis with descriptive ethnobotany, the study investigates how plant community structure correlates with the medicinal potential of the species in the area. Vegetation data were obtained by placing 2 × 2 m plots (4 m²) at 200-meter intervals along the trail, alternating between the left and right sides. The vegetation analysis calculated density, frequency, and the Important Value Index (IVI) to evaluate the dominance of species. Ethnobotanical information was collected through direct field observations and a review of existing ethnobotanical and ethnopharmacological literature, without conducting formal interviews. The results show that the medicinal plant community is dominated by species with high IVI values, such as Chloranthus officinalis, Piper nigrum, and Elephantopus mollis. These species act as key elements in the understory and have been widely recognized for their medicinal uses in traditional practices. Their ecological dominance indicates strong adaptability to the moderate disturbances of the trail environment. The combined use of IVI analysis and ethnobotanical data underscores that species with higher ecological dominance are more likely to have significant medicinal uses, offering valuable insights for the sustainable management and conservation of medicinal plants along MRNP's tourist trails.